CONSTRUÇÃO DE UM INDICADOR PARA A QUALIDADE GLOBAL DE VIDA NO ENSINO PÚBLICO SUPERIOR (Estudo de Caso sobre as condições de vida e trabalho vinculadas à formação de profissionais do Curso de Graduação em Matemática da Universidade Federal Fluminense) - Silva, Licinio Esmeraldo da (2006)
A quality of life index is presented and applied to students and teachers of a university. The index, supported by four dimensions of quality of life, emerges from the crossing of two dichotomies of human beings: individual life-occupational life versus physical dimensionpsychic dimension. This crossing action makes emerge four planes to considering quality of life. The individual physical life was available by the instrument WHOQOL-Bref; the individual psychic one by SRQ-20, the occupational physical one by a ponometric scale and the occupational psychic one by a scale for detecting stress (students) or by the Maslach Burnout Inventory scale (teachers). The results show that, except on the individual psychic dimension, female groups present precarious quality of life in relation to males ones (p<0,05). It was observed around 20% of peoples in suffering stage on each of the four dimensions. The global quality of life (GQL) index shows that individual and occupational conditions of life of the students are worst of teachers one (p<0,05).